Diabetes websites lack information on dietary causes, risk factors, and preventions for type 2 diabetes - Crummett, Lisa T.; Aslam, Muhammad H. (Frontiers in Public Health, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is a growing public health burden throughout the world. Many people looking for information on how to prevent T2DM will search on diabetes websites. Multiple dietary factors have a significant association with T2DM risk, such as high intake of added sugars, refined carbohydrates, saturated fat, and red meat or processed meat; and decreased intake of dietary fiber, and fruits/vegetables. Despite this dietary information being available in the scientific literature, it is unclear whether this information is available in grey literature (websites). Objective: In this study, we evaluate the use of specific terms from diabetes websites that are significantly associated with causes/risk factors and preventions for T2DM from three term categories: (A) dietary factors, (B) nondietary nongenetic (lifestyle-associated) factors, and (C) genetic (non-modifiable) factors. We also evaluate the effect of website type (business, government, nonprofit) on term usage among websites. Methods: We used web scraping and coding tools to quantify the use of specific terms from 73 diabetes websites. To determine the effect of term category and website type on the usage of specific terms among 73 websites, a repeated measures general linear model was performed. Results: We found that dietary risk factors that are significantly associated with T2DM (e.g., sugar, processed carbohydrates, dietary fat, fruits/vegetables, fiber, processed meat/red meat) were mentioned in significantly fewer websites than either nondietary nongenetic factors (e.g., obesity, physical activity, dyslipidemia, blood pressure) or genetic factors (age, family history, ethnicity). Among websites that provided “eat healthy” guidance, one third provided zero dietary factors associated with type 2 diabetes, and only 30% provided more than two specific dietary factors associates with type 2 diabetes. We also observed that mean percent usage of all terms associated with T2DM causes/risk factors and preventions was significantly lower among government websites compared to business websites and nonprofit websites. Conclusions: Diabetes websites need to increase their usage of dietary factors when discussing causes/risk factors and preventions for T2DM; as dietary factors are modifiable and strongly associated with all nondietary nongenetic risk factors, in addition to T2DM risk.